Influence of end-stage renal disease on long-term survival after major amputation - Meyer, Alexander; Griesbach, Colin; Maudanz, Nils; Lang, Werner; Almási-Sperling, Veronika; Rother, Ulrich (Vasa-Journal of Vascular Diseases, 2020)
Background: To analyze long-term outcomes and possible influencing factors in patients with endstage renal disease (ESRD) and critical limb ischemia (CLI) after major amputation compared to patients with normal renal function and non-dialysis-dependent chronic kidney disease. Patients and methods: Abstraction of single-center medical records of patients undergoing above knee (AKA) and below knee (BKA) amputation over a 10 years period (n = 436; 2009-2018). Excluded were amputations due to trauma or tumor. Patients were subdivided according to renal function in three categories: ESRD patients (n = 98), non-dialysis dependent chronic kidney disease (CKD, n = 98) and normal renal function (NF, n = 240). Predefined endpoints were survival and postoperative complications. Cox-regression models were built to analyze independent risk factors for outcome parameters. Results: In total, 298 AKA, 133 BKA and 5 knee joint exarticulations were performed. ESRD patients showed inferior in-hospital results as to death (ESRD 36.7 % vs. CKD 19.4 % and NF 20.0 %, P = .002). Similarly, long-term survival rates (6 months: ESRD 55.0 % vs. CKD 69.4 %, NF 67.9 % 1 year: ESRD 48.6 %, CKD 60.2 %, NF 60.8 % 5 years: ESRD 9.9 %, CKD 31.8 %, NF 37.1 %, P < .001) were significantly decreased for ESRD patients. Median postoperative survival was 10 months in ERSD, and 22 months in CKD and NF, respectively. Analysis of postoperative surgical complications revealed no differences between groups (ESRD 19.4 %, CKD 17.3 %, NF 17.0 %; P = 0.433). Cox regression analysis indicated that dialysis (HR 1.63; 95 % CI 1.22-2.16; P = .001), hypertension (HR 1.59; 95 % CI 0.99-2.54) and smoking (HR 1.22; 95% CI 1.03-1.44; P = .022) was associated with increased risk of death during follow-up. Conclusions: Mortality after limb amputation in ERSD patients remains high. Survival of ERSD patients is lower in relation to chronic kidney disease and patients with normal renal function. Due to poor in hospital outcomes and absent long-term survival, benefit of primary amputation in ERSD seems scarce.
CRIS-Team Scopus Importer:2020-07-10
Keywords: amputation; critical limb ischemia; dialysis; outcome; Vascular